Phagocyte Activity in Response to Exposure to Methicillin-Resistant Staphylococcus aureus Strains - O. A. Kolenchukova; V. D. Belenuk (Антибиотики и Химиотерапия, 2022)
The research focuses on the study of phagocyte activity of blood neutrophilic granulocytes, monocytes, and eosinophils under the exposure to methicillin-resistant strains of Staphylococcus aureus bacteria. The subjects of the research were represented by blood neutrophilic granulocytes, monocytes, and eosinophils, isolated from healthy people, as well as methicillin-resistant and methicillin-sensitive S.aureus bacteria strains  (MRSA and MSSA). Phagocytosis functions (phagocytic number and phagocytic index)  were estimated by FITC-labeled bacteria. The analysis of stained cells was performed using  FC-500 flow cytofluorimeter (Beckman Coulter,  USA) for whole  peripheral blood. Phagocytosis research  resulted in the following findings. In response to MRSA, the percentage of neutrophils involved in phagocytosis and average  number of bacteria being  present inside the cells  increase as compared to those within  sensitive strains. In response to MRSA exposure, the phagocytic index  is higher  in monocytes with CD14+CD16¯phenotype. At the same time, phagocytic number is higher in non-classic populations of monocytes CD14+CD16+and CD14lowCD16+. Moreover, it should be noted that the classical type of monocytes CD14+CD16¯tends to be activated faster in regard to MRSA, but phagocytosis efficiency is lowered. Blood eosinophils also actively respond to MRSA. Thus, changes in functional activity of neutrophilic granulocytes, monocytes, and eosinophils in peripheral blood were established during MRSA induction. The bacterial receptor apparatus changes due to the modification of cellular wall as a result of acquired resistance to antibiotics.